INNOVATION AND OPERATIONS. COMPARATIVE ANALYSIS - L. Zelentsova; A. Goloskov (Вестник университета)
The article gives a brief description of the current domestic and international position of Russia in relation to innovation. It raised the question of determining the sources of increase of efficiency in the internal environment of the companies involved in the innovation process and management, provides the organization and maintenance of its implementation. The comparative analysis of the objectives of the organization in terms of the operational and management innovation.